Citra Perempuan Suku Dani dalam Novel Etnografi Sali: Kisah Seorang Wanita Suku Dani Karya Dewi Linggasari: Analisis Kritik Sastra Feminis Ruthven - Devita Hermawati; Rudi Ekasiswanto (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2013)
Various kinds of ways to criticize gender inequality and women received a patriarchal culture, onethrough literary works. In Sali: Kisah Seorang Wanita Suku Dani (SKSWSD) an ethnographic novel,the author tried to criticize the gender inequality that is represented by women figures in the story so asto form the image of Dani women. This ethnographic novel SKSWSD background during the monetarycrisis, the conditions of civilization and progress began to enter and thrive in Wamena. At that time,there is still growing strong patriarchal culture in the Dani. Dani women live a hard life in the midst ofa patriarchal system. Dani women's double burden as indigenous actors, namely taking care ofdomestic and earn a living.